T2/FLAIR Hyperintensity in Mesial Temporal Lobe: Challenging Differential Diagnosis - Moon, Sungjun (Current Medical Imaging, 2022)
T2/FLAIR hyperintensity in the mesial temporal lobe is the most common MR finding of herpes simplex encephalitis, but may be observed in other infectious and non-infectious diseases. The former includes herpes human virus 6 encephalitis, Japanese encephalitis, and neurosyphilis, and the latter autoimmune encephalitis, gliomatosis cerebri, bilateral or paradoxical posterior cerebral artery infarction, status epilepticus, and hippocampal sclerosis. Thus, T2/FLAIR hyperintensity in the mesial temporal lobe is not a disease-specific magnetic resonance imaging finding, and these conditions must be differentiated to ensure proper treatment. We review diseases that present with T2/FLAIR hyperintensity in the mesial temporal lobe and provide a helpful flow chart based on clinical and radiologic features.
Keywords: Japanese encephalitis